Novel spinal cord stimulation system with a Battery‐Free micro‐implantable pulse generator. - Malinowski, Mark N.; Heit, Gary; Poree, Lawrence R.; Makous, James; Amirdelfan, Kasra (Pain Practice, 2022)
Spinal cord stimulation (SCS) is effective for the treatment of chronic intractable pain of the trunk and limbs. The mechanism of action may be based, at least in part, upon the gate control theory; however, new waveforms may suggest other mechanisms. Although benefits of the SCS technology generally outweigh the complications associated with SCS, some complications such as infection and skin erosion over the implant can result in device removal. Additional reasons for device removal, such as pocket pain and battery depletion, have driven technological innovations including battery‐free implants and device miniaturization. The neurostimulation system described here was specifically designed to address complications commonly associated with implantable batteries and/or larger implantable devices. The benefits of the small size are further augmented by a minimally invasive implant procedure. Usability data show that patients found this novel neurostimulation system to be easy to use and comfortable to wear. What is more, clinical data demonstrate that the use of this system provides statistically significant reduction in pain scores with responder rates (defined as ≥50% reduction in pain) of 78% in the low back and 83% in the leg(s). Advances in miniaturization technology arose from the considerable shrinkage of the integrated circuit, with an increase in performance, according to Moore's law (1965). However, commensurate improvements in battery technology have not maintained a similar pace. This has prompted some manufacturers to place the battery outside, against the skin, thereby allowing a massive reduction in the implant volume, with the hopes of fewer device‐related complications.